Physical activity in pregnant women with Class III obesity: A qualitative exploration of attitudes and behaviours. Issue 12 (December 2015) - Denison, F.C.; Weir, Z.; Carver, H.; Norman, J.E.; Reynolds, R.M.
Abstract: Objective: to explore the barriers and facilitators to physical activity and lifestyle interventions in pregnant women with Class III obesity (body mass index >40 kg/m 2 ). Design: qualitative study using in-depth, semi-structure interviews framed by the Theory of Planned Behaviour. Semi-structured, in-depth interviews were conducted using a topic guide. Data analysis was undertaken using a Framework Approach and was informed by the theory of planned behaviour. Recruitment and analysis continued until data saturation was reached. Setting: participants were recruited from an antenatal clinic for women with Class III obesity. Participants: pregnant women ( n =13) with Class III obesity. Measurements and outcomes: three major themes emerged from the data analysis: having a healthy lifestyle awareness, complex barriers to lifestyle changes and having personalised solutions to promote healthy lifestyle. Women were aware of the benefits of physical activity during pregnancy but had complex barriers to engaging with activity. Conclusions and implications for practice: future lifestyle interventions for women with Class III in pregnancy should take into account individual, societal and support barriers towards weight management and lifestyle choices in pregnancy. Programs that provide personalised support which are sensitive to the specific physical and psychological needs of women with Class III obesity which focus on the benefits and safety of physical activity for both mother and baby may be more likely to be successful. Further research is needed to explore the feasibility and acceptability of tailored programs. Highlights: Women with Class III obesity are aware of the benefits of physical activity. Most women with Class III obesity have complex barriers to engaging with exercise. Several women described issues surrounding their body size and image. Women with Class III obesity have different perceptions of what constitutes exercise. Women value personalised solutions for exercise programs.